Equidade educacional nos territórios vulneráveis do município de São Paulo - Rocha, Andreza Maria de Souza (2021)
The objective of this research is to verify if the city of São Paulo expanded educational equity in the early years of elementary school, in the municipal network, in relation to Portuguese language learning, and how this situation is verified in schools located in contexts of social vulnerability. For Dubet (2009), Crahay (2000) and Ribeiro (2014), the principle of justice most appropriate to educational policies in basic education is the basic equality/equality of acquired knowledge, a principle that, according to Ribeiro (2014), adjusts to justice as equity proposed by Rawls (2003). Regarding social vulnerability, experts point out that this phenomenon affects student performance (ÉRNICA; BATISTA, 2012; RIBEIRO; VÓVIO, 2017), which makes the realization of justice as equity complex, according to Pereira-Silva (2016). This research is quantitative in nature and, to understand the evolution of the equity situation in the city of São Paulo and in its vulnerable territories, an index of educational equity and an index of social vulnerability (ISV) were related. For Penninck (2019), the municipal education network in São Paulo has expanded its capacity to generate learning for everyone, including children with lower socioeconomic status (SES) and schools located in vulnerable territories. There are indications that, considering the differences in the SES of the students, the network is closer to the notion of a fairer school, in which all children, regardless of their social background, reach the level of learning considered adequate by the State. Corroborating Penninck (2019), this research identifies that equity in the early years of elementary school was expanded in the municipal network of the city of São Paulo, independent of the IVS, between 2011 and 2017. However, the traditional gaps between social groups remain. and place of residence. Boys, blacks, and residents of vulnerable territory are at a disadvantage.